PENGARUH KEGIATAN KONSULTASI TERHADAP TINGKAT KECEMASAN PADA KELUARGA PASIEN YANG DIRAWAT DI RUANG ICU RSUD WALED KABUPATEN CIREBON - Lili Amaliah; Ricky Richana (LPPM ITEKES Mahardika, 2018)
Background: Intensive Care Unit (ICU) is a hospital section equipped with specialized staff and specialized equipment aimed at observing, treating and treating patients suffering from life-threatening, potentially life-threatening, life-threatening or life-threatening complications or complications. reversible. Anxiety in the patient's family in the ICU room will cause a new problem, anxious family families will experience a variety of disorders. For families of patients who are in critical care paients in reality have high emotional stress. Getting information about the patient's medical condition and the relationship with the service provider is the highest priority expected and needed by the patient's family. Purpose: To find out the influence of nursing consultation activity on patient anxiety level of patient family in ICU Room Waled Hospital Cirebon Regency. Method: This research used quasi experiment with pre and post test design with uot control group. The study was conducted in ICU district of RSUD Waled/ In this study used the total sampling technique in which the entire population as the respondents the patient's family in ICU Room of the research are as many as 37 respondents. Result: The results showed that the anxiety that occurred in the patient's family before the consultation activity was mostly in moderate anxiety (45.94%) with median value 31.04. Anxiety that occurred in the patient's family after the Consultation Activities were mostly in the minor anxiety (51.35%) with median value of 37.48. Anxiety before and after intervention has p value 0.017 or smaller than 0.5 so Ho is rejected. Conclusion: Its mean that the consultation activities can affect the level of anxiety in the patient's family in ICU Room